Online professional education: A case study of an MBA program through its transition to an online model - Schrum, Lynne; Benson, Angela (Online Learning, 2000)
Recently a large corporation joined with a large southeastern university’s College of Business MBA program to create a distance MBA program uniquely suited to the corporation's high level workers’ needs to obtain the degree while they continue working. This corporation invested significantly in the design and development of this tailored program which includes online and face-to-face components. This paper reports on research on the first year of this pilot program from the faculty, administrative, and student perspectives. Conclusions are given and suggestions are made for further research.